Ladder limit for correlators of Wilson loops - Correa, Diego Hernán (2018)
We study the correlator of concentric circular Wilson loops for arbitrary radii, spatial and internal space separations. For real values of the parameters specifying the dual string configuration, a typical Gross-Ooguri phase transition is observed. In addition, we explore some analytic continuation of a parameter γ that characterizes the internal space separation. This enables a ladder limit in which ladder resummation and string theory computations precisely agree in the strong coupling limit. Finally, we find a critical value of γ for which the correlator is supersymmetric and ladder diagrams can be exactly resummed for any value of the coupling constant.